The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1471-2334-13-594
|View full text |Cite
|
Sign up to set email alerts
|

A case of subacute infective endocarditis and blood access infection caused by Enterococcus durans

Abstract: BackgroundInfection by Enterococcus durans (E. durans) is very rare; reported cases are often preceded by therapy or an immunosuppressed state, including infective endocarditis, urinary tract infection, or wound infection. A few reported cases of infective endocarditis exist, with no reports describing involvement of blood access infection.Case presentationThe patient is an 83-year-old man who had been undergoing hemodialysis for 8 years due to renal failure caused by diabetic nephropathy. He developed infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 10 publications
1
16
1
Order By: Relevance
“…In addition, regular needle punctures during hemodialysis may provide a means for bacteria to enter the bloodstream. However, some authors have reported that infections affecting arteriovenous fistulas cause bloodstream infections (14), although the contrast-enhanced CT scans did not suggest a fistula infection in the present patient.…”
Section: Discussioncontrasting
confidence: 47%
“…In addition, regular needle punctures during hemodialysis may provide a means for bacteria to enter the bloodstream. However, some authors have reported that infections affecting arteriovenous fistulas cause bloodstream infections (14), although the contrast-enhanced CT scans did not suggest a fistula infection in the present patient.…”
Section: Discussioncontrasting
confidence: 47%
“…Almost all studies on bacteremia in Japan were case reports[11-13]. Sepsis was the second leading cause of death in infectious diseases in a study in Japan[14].…”
Section: Incidence Of Bacteremia In Hemodialysis Patientsmentioning
confidence: 99%
“…This organism (formerly Streptococcus durans) is an exceptional cause of human disease. It was anecdotally described as an agent of bacteremias (3), urinary tract infections (4), wound infections (5), and four endocarditis cases (6). Also, it has been found in dairy products and in human and animal milk microbiota (6)(7)(8).…”
mentioning
confidence: 99%
“…It was anecdotally described as an agent of bacteremias (3), urinary tract infections (4), wound infections (5), and four endocarditis cases (6). Also, it has been found in dairy products and in human and animal milk microbiota (6)(7)(8). E. durans appears as elongated nonmotile cells that are mostly arranged in pairs and short chains; it forms circular, smooth, entire, and nonpigmented colonies when grown on a blood medium, showing the Lancefield group D and, occasionally, group G antigen (8,9).…”
mentioning
confidence: 99%